Impairment of Grapevine Xylem Function by Phaeomoniella chlamydospora Infection Is Due to More than Physical Blockage of Vessels with ’Goo’ - Edwards, J.; Pascoe, I.G.; Salib, S. (Phytopathologia Mediterranea, 2007)
Phaeomoniella chlamydospora is a vascular pathogen that colonises the woody xylem tissues of the grapevine. It is associated with the grapevine trunk diseases, esca and Petri disease. Infection is usually accompanied by a dark tarry substance, commonly refered to as ‘black goo’, in some of the xylem vessels. Examination of field grown Verdelho demonstrated that infection reduced xylem function by 16% for each 1% increase in ‘goo’-blocked vessels, indicating that vessel blockage is not solely responsible for loss of xylem function.